New perspective on conceptus estrogens in maternal recognition and pregnancy establishment in the pig†. Issue 1 (10th April 2019) - Meyer, Ashley E; Pfeiffer, Caroline A; Brooks, Kelsey E; Spate, Lee D; Benne, Joshua A; Cecil, Raissa; Samuel, Melissa S; Murphy, Clifton N; Behura, Susanta; McLean, Megan K; Ciernia, Lauren A; Smith, Michael F; et al.
Abstract: The proposed signal for maternal recognition of pregnancy in pigs is estrogen (E2), produced by the elongating conceptuses between days 11 to 12 of pregnancy with a more sustained increase during conceptus attachment and placental development on days 15 to 30. To understand the role of E2 in porcine conceptus elongation and pregnancy establishment, a loss-of-function study was conducted by editing aromatase ( CYP19A1 ) using CRISPR/Cas9 technology. Wild-type ( CYP19A1 +/+ ) and ( CYP19A1 −/− ) fibroblast cells were used to create embryos through somatic cell nuclear transfer, which were transferred into recipient gilts. Elongated and attaching conceptuses were recovered from gilts containing CYP19A1 +/+ or CYP19A1 − / − embryos on day 14 and 17 of pregnancy. Total E2 in the uterine flushings of gilts with CYP19A1 − / − embryos was lower than recipients containing CYP19A1 +/+ embryos with no difference in testosterone, PGF2α, or PGE2 on either day 14 or 17. Despite the loss of conceptus E2 production, CYP19A1 − / − conceptuses were capable of maintaining the corpora lutea. However, gilts gestating CYP19A1 − / − embryos aborted between days 27 and 31 of gestation. Attempts to rescue the pregnancy of CYP19A1 − / − gestating gilts with exogenous E2 failed to maintain pregnancy. However, CYP19A1 − / − embryos could be rescued when co-transferred with embryos derived by in vitro fertilization. Endometrial transcriptome analysis revealed that ablation of conceptus E2 resulted in disruption of a number biological pathways. Results demonstrate that intrinsic E2 conceptus production is not essential for pre-implantation development, conceptus elongation, and early CL maintenance, but is essential for maintenance of pregnancy beyond 30 days . Abstract : Ablation of pig conceptus estrogen production does not affect early maternal recognition of pregnancy and conceptus development but causes a ripple effect in conceptus/endometrial programming resulting in failure to maintain pregnancy beyond 30 days of gestation.